2015
DOI: 10.1111/jace.13939
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Microstructure of Hydrated Phases During the Pozzolanic Reaction in the Sanitary Ware Waste/Ca(OH)2 System

Abstract: Despite technological improvements in its production process, the sanitary ware industry inevitably generates a certain volume of discards, products whose quality is not up to standard. The present paper is the first to scientifically explore clay‐based sanitary ware waste (SW) with a view to its valorization as an addition in the design of new, more environmentally friendly cements. The focus is on characterization of the waste and its pozzolanicity, as well as the structural and microstructural changes takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 66 publications
(117 reference statements)
3
8
0
Order By: Relevance
“…16c. This illustrates the pozzolanic reaction of Si and Al with Ca +2 cations, which encourages further dissolution and breaking the Si-O and Al-O bonds in both MK and NP [77]. Ak products can be distinguished clearly as a predominant phase of flat continuous gels in all blends, but its lowest appearance can be seen in AAC11, which agrees with the XRD patterns.…”
Section: Sem Analysis Of Hydratessupporting
confidence: 80%
“…16c. This illustrates the pozzolanic reaction of Si and Al with Ca +2 cations, which encourages further dissolution and breaking the Si-O and Al-O bonds in both MK and NP [77]. Ak products can be distinguished clearly as a predominant phase of flat continuous gels in all blends, but its lowest appearance can be seen in AAC11, which agrees with the XRD patterns.…”
Section: Sem Analysis Of Hydratessupporting
confidence: 80%
“…The main difference between the two spectra was that the Q1 unit signal was much more intense in the OPC than in the 20% ACW cement paste, denoting a smaller proportion of end of chain units and hence a higher degree of polymerization in the latter. Other authors have reported similar results for the pozzolanic reaction in fired clay-based waste [34]. Furthermore, the amount, distribution and microstructural characteristics of the C-S-H gel formed have a significant effect on the mechanical strength of the cement.…”
Section: Micro-ramansupporting
confidence: 68%
“…Fired clay industry waste is one of the new pozzolans explored by researchers. A number of prior studies on this material showed that fired clay of different origins has very promising pozzolanic properties because when fired at temperatures of 600°C‐900°C and ground to cement fineness, initially inert clay minerals acquire substantial pozzolanicity . The evaporation of chemically combined water at such temperatures and the resulting breakdown of the crystalline network of clay constituents induces the formation of an amorphous or vitreous material.…”
Section: Introductionmentioning
confidence: 99%